Understanding the lithiation/delithiation process in SnP2O7 anode material for lithium-ion batteries. (20th October 2017) - Bezza, Ilham; Trouillet, Vanessa; Fiedler, Andy; Bruns, Michael; Indris, Sylvio; Ehrenberg, Helmut; Saadoune, Ismael
Abstract: Anode materials based on silicon or tin, with distinctively higher theoretical specific capacities of 700 mAh/g compared to the commonly used graphite in Lithium-ion batteries exhibiting limited capacity of 370 mAh/g, are presently in the focus of intensive research studies as new anode materials. In the present work, coated and non-coated tin pyrophosphate materials were successively prepared and their electrochemical performance were compared. The use of carbon coating generally results in an improved cycling stability and a decrease in particles size. The X-ray diffraction patterns of the two samples are similar as indication of an amorphous character of the residual carbon. The scanning electron microscopy images of the both samples show a small particle size (nanometric) and the layers of the graphite are clearly observed. Raman spectroscopy was carried out to identify the D and G bands related to the graphite. X-ray photoelectron spectroscopy (XPS) was used to follow the Sn bonding/valence changes during discharge-charge process and also to identify the SEI layer which is formed at the last step of the discharge process.